ANALISIS JIWA KEWIRAUSAHAAN PENGUSAHA KECIL DI DESA SUKA MAJU KECAMATAN RAMBAH KABUPATEN ROKAN HULU - FIDIANA, NIA (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This study aims to determine the level of entrepreneurial spirit small entrepreneurstraders in improving their business in the village of Suka Maju Rambah District of RokanHulu and this includes research into quantitative categories. The focus of this study wasto measure the entrepreneurial spirit of small, the entire study population was smallentrepreneurs in the village Suka Maju Rambah Rokan Hulu District. And the number ofsamples is determined by 30 people using quota sampling (quota sampling). Of all surveyrespondents on average were women, young age, and level of education has been througha 9 year compulsory education. The results of the 30 small entrepreneurs obtained resultsstatement item count R> R table, validity test performed using SPSS 18 that all validitem. And the results of reliability test is known that the item variable statement reliablebecause the Cronbach alpha values â‰¥ 0.60 is 0.754. achievement level of all indicatorsrespondents on average above 80% with a good description except in the dimension ofrisk-taking in an innovative and flexible indicator of the level of achievement is onlybetween 75-80% of the respondents or the description pretty well. Especialicy in the fieldof small bussines entrepreneurships to be more innovative and flexible to support thesuccess and continuation of their bussines